GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2016)
A dataset containing 17420 species occurrences available in GBIF matching the query: TaxonKey: Pertusaria albescens (Huds.) M. Choisy & Werner HasCoordinate: TRUE HasGeospatialIssue: FALSE. The dataset includes 17420 records from 100 constituent datasets: 2 records from Specimens of lichen herbarium KPABG. 11 records from Jordal. 22 records from Dorset SSSI Species Records 1952 - 2004 (Natural England). 110 records from BLS Lichen Database: Welsh churchyards. 24 records from Dorset Sites of Nature Conservation Interest (SNCI) species records pre 2000. 8 records from HBRG Fungus, Lichen & Lower Plants Dataset. 5 records from Naturalis Biodiversity Center (NL) - Botany Leiden. 3 records from PlutoF platform observations. 99 records from Colección de líquenes del Herbario "Jaime Andrés Rodríguez". LEB-Lichen. 2 records from Lichen diversity in forests. 14 records from BioFokus. 485 records from Artdata. 1 records from OHN. 2 records from Données ONF Faune-Flore-Fonge. 1702 records from BLS Lichen Database: English churchyards. 7 records from Australia's Virtual Herbarium. 6 records from Estonian Museum of Natural History. 2 records from tree climbing bryophytes & lichens at tree base and crown with traits. 1 records from Lillachtal mit Kalktuffquelle bei Weißenohe. 1 records from University of British Columbia Herbarium (UBC) - Lichen Collection. 1 records from Rotes Steigle (Panzerübungplatz Böblingen). 1 records from FFH-Gebiet "Calwer Heckengäu". 1 records from GEO-Hauptveranstaltung im Nationalpark Bayerischer Wald. 1 records from Biosphärenpark Wienerwald - Wiener Steinhofgründe. 1 records from Countryside Council for Wales - Phase 2 Lowland Grassland Survey of Wales. 25 records from naturgucker. 10 records from Institut Botanic de Barcelona (IBB-CSIC-ICUB), BC-Lichen. 2 records from RHS monitoring of native and naturalised plants and animals at its gardens and surrounding areas. 9 records from National Trust - Hatfield Forest species data held by The National Trust.. 1 records from Biosphärenpark Wienerwald - Pfaffstätten. 3 records from Dutch Vegetation Database (LVD). 2 records from INPN - Données flore des CBN agrégées par la FCBN. 60 records from Lichen herbarium, NTNU University Museum. 20 records from Lichen herbarium, Oslo (O). 4 records from Dorset Sites of Nature Conservation Interest (SNCI) species records 2000-2008. 7 records from IBF Monitoring of Lichens. 3 records from The Lichen Collection at the Botanische Staatssammlung München. 8 records from BRERC species records recorded over 15 years ago. 5 records from Natural History Museum (London) Collection Specimens. 1 records from Natural History Museum, Vienna - Herbarium W. 6 records from Ireland's BioBlitz. 26 records from Karl Franzens University of Graz, Insitute for Botany - Herbarium GZU. 46 records from Herbarium Senckenbergianum (FR) - Fungi. 1 records from Canadian Museum of Nature Herbarium. 2553 records from BLS Lichen Database: Scotland. 1 records from Herbarium (AMNH). 96 records from Real Jardin Botanico, Madrid: MA-Lichen. 20 records from Departamento de Biolog. Veg. II, Facultad de Farmacia, Universidad Complutense, Madrid: MAF-Lich. 1 records from Michigan State University Herbarium Lichens. 32 records from Arizona State University Lichen Collection. 3 records from Botanical Museum, Copenhagen, the Lichen Herbarium. 41 records from Danish Mycological Society, fungal records database. 115 records from Lichen Herbarium Berlin. 509 records from Biologiezentrum Linz. 157 records from LiquenCAT: Banco de datos de los líquenes de Cataluña. 1 records from Epiphytic Lichens of G. Lettau at the Botanical Museum Berlin-Dahlem. 1 records from The Collection of Lichenicolous Fungi at the Botanische Staatssammlung München. 156 records from Universitat de València, Colecciones de Criptógamas: VAL_Lich. 347 records from FloVegSI - Floristical and fitocenological database of ZRC SAZU. 1 records from Danielsberg (Mölltal, Kärnten). 1 records from Waldränder der Frankenhöhe (Rothenburg ob der Tauber). 1 records from Gemeinde Sursee. 1 records from GEO Hauptveranstaltung Tirol (Innsbruck). 1 records from Zukünftiges NSG Höftland/Bockholmwik. 1 records from Erlengraben/Lipp-Tal (Östringen). 1 records from Neckartalsüdhang (Horb). 1 records from Unser Schulgelände. 32 records from Lichens of North-Eastern Poland. 203 records from Natural History Museum, University of Tartu. 16 records from Lichens of Biebrza National Park. 26 records from Herbarium of Umeå University (UME). 3739 records from BLS Lichen Database: England. 107 records from Banco de Datos de la Biodiversidad de la Comunitat Valenciana. 2 records from Lichen Collection - University of Washington Herbarium (WTU). 4522 records from BLS Mapping Scheme dataset, 1750-2009. 1 records from Herbarium of the Department of Natural Forests (Forest Research Institute) - Lichens. 1316 records from BLS Lichen Database: Wales. 7 records from ARKO gamle edellauvtrær. 217 records from Lund Botanical Museum (LD). 1 records from National Trust - Ickworth species data held by The National Trust.. 16 records from Norwegian Species Observation Service. 26 records from Lichens of Knyszyn Forest. 4 records from Staffordshire Ecological Record - SER Species-based Surveys. 22 records from Lichens from Russian Fennoscandia. 1 records from Royal Botanic Garden Edinburgh Herbarium (E). 3 records from LNHG Biological Records Dataset. 15 records from Lichen herbarium, NMBU. 2 records from Countryside Council for Wales - Welsh Invertebrate Database (WID). 18 records from Herbarium WRSL, Lichens Collection. 2 records from Données ONF Faune-Flore-FOnge. 1 records from Lichen field notes, Oslo (O). 2 records from Ecofact. 15 records from Suffolk Biodiversity Information Service (SBIS) Dataset. 2 records from Lichen herbarium, Tromsø Museum. 2 records from Fungi of Costa Rica (INBio). 8 records from National Trust for Scotland Species Records. 13 records from Geneva Herbarium – General Collection (G). 13 records from BRERC species records within last 15 years. 110 records from Lichen herbarium, UiB. 164 records from Fungi (S). Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences